O processamento da informação na webnotícia - Maria Lourdilene Vieira (2015)
In this thesis, we aim as general objective of research at examining the information processing in web news, in cases where the information comes from one main source text and thus exemplify the process of retextualization. For this, we are based on two main theoretical strands. In textual perspective, about the process of retextualization, we followed Marcuschi (2000 [2010]), Dell'Isola (2007) and Matêncio (2002; 2003), and still consider the assumptions of Van Dijk (1990 [1988]) and Gomes (1995), on the processing of information. From the perspective of genres, we are based on the socio-rhetorical theory according to Miller (2009 [1984]), Devitt (2004) and Bazerman (2005), and in terms of Swales (1990), Askehave & Swales (2009) and Bhatia (2009). The analysis corpus was organized according to criteria of qualitative nature, with 21 examples of the news genre published in journalistic portals and their main source texts. Regarding to the retextualization process, strategies for elimination, addition, substitution and reordering in web news were analyzed, and regarding to the functioning of the genre, we consider the fusion of form and substance, the recurring rhetoric situation, the social action and the communicative purpose. At this stage, we still did the analysis of the set of information obtained from responses from journalists, experienced web news users, to the questionnaire developed by us. The main results showed that the strategies used by retextualization rhetor for construction of web news have in mind the constraints and specificities of the genre, which ends by driving the strategies used for processing, which results in an adaptation of the text information source for web news. This adjustment sets the processing of information in the construction of web news and can be examined in the genre, once it happens according to the formal and substantive features of it. The use of the source text in web news works, among others, to print truthfulness to what is reported, once it can be used as part or as the news itself. However, the criteria for newsworthiness are linked to the need for a hearing, which contributes to the choice of having more or less relevant to be publicized by web news is more related to the possibility to attract the attention of netizens than the importance of information for society.